Koncept v družino usmerjene obravnave in ocena postopkov oskrbe - Groleger Sršen, Katja (Rehabilitacija (Ljubljana), 2015)
Background: Chronic disease has a significant impact on a child's overall development, but also on functioning of the entire family. A family-centred service is a concept of work developed during the last decades. We wanted to check how parents evaluate the processes of care in the treatment and rehabilitation programs in several medical institutions across Slovenia. Methods: Parents of children who were referred to several medical institutions for the treatment and (re)habilitation were invited to participate in the study. For the assessment of processes of care we used the Slovenian translation of the MPOC-20 questionnaire (Measures of Processes of Care), which was completed by the parents. Results: There were 235 parents who decided to participate in the study. They reported high overall satisfaction with processes of care, but also pointed out some of the areas that were less satisfactory. Parents reported lower scores on two MPOC-20 subscales - providing general information and providing specific information about the child. Conlusions: Parents were least satisfied with providing information in the processes of care. For this reason, we are planning to organise an educational program for service providers in order to improve the processes of care.
Keywords: child; evaluation; MPOC-20; ocenjevanje; otroci; Parents; postopki oskrbe; processes of care; Slovenia; Slovenija; starši